Physiological and psychological adaptations during taper in competitive swimmers - Myers, V. R.; Wells, G. D.; McKillop, A. L.; Fraser, S. J.; Abel, J. M. (International Journal of Sports Science & Coaching, 2017)
An effective taper in training load is essential for increased performance outcomes at competition, however optimal taper individualization remains elusive. Monitoring psychological and physical adaptations that occur during the taper may help guide the optimization of training during a taper resulting in improvements in performance. We monitored physical and psychological variables as well as competition performance of 10 elite swimmers before and during a 21-day taper in preparation for the Canadian National Championships or World Championships. Mood and recovery were assessed using the Brunel Mood Scale and the Recovery-Stress Questionnaire. Resting muscle tension, skin conductance, and respiration rate were measured using biofeedback technology. Speed and heart rate were assessed with a 2 × 200 m submaximal swim test. Resting HR was measured using the Rusko test. We hypothesized that psychological and physiological measurements would change during the taper phase and that these changes would be associated with improved competition performance. Results showed that the Brunel Mood Scale, Recovery-Stress Questionnaire, 2 × 200 m submaximal test, and the Rusko test changed significantly throughout the taper period. Variables from the Brunel Mood Scale and the Recovery-Stress Questionnaire showed a significant relationship with improved performance, indicating that these questionnaires show good utility for assessing progress during a taper in the future. ABSTRACT FROM AUTHOR